Co-applied biochar and drought tolerant PGPRs induced more improvement in soil quality and wheat production than their individual applications under drought conditions - Laraib Malik; Sabir Hussain; Muhammad Shahid; Faisal Mahmood; Hayssam M. Ali; Mehreen Malik; Muhammad Sanaullah; Zubda Zahid; Tanvir Shahzad (PeerJ, 2024)
Background Plant growth and development can be greatly impacted by drought stress. Suitable plant growth promoting rhizobacteria (PGPR) or biochar (BC) application has been shown to alleviate drought stress for plants. However, their co-application has not been extensively explored in this regard. Methods We isolated bacterial strains from rhizospheric soils of plants from arid soils and characterized them for plant growth promoting characteristics like IAA production and phosphate solubilization as well as for drought tolerance. Three bacterial strains or so called PGPRs, identified as Bacillus thuringiensis, Bacillus tropicus, and Bacillus paramycoides based on their 16S rRNA, were screened for further experiments. Wheat was grown on normal, where soil moisture was maintained at 75% of water holding capacity (WHC), and induced-drought (25% WHC) stressed soil in pots. PGPRs were applied alone or in combination with a biochar derived from pyrolysis of tree wood. Results Drought stress substantially inhibited wheat growth. However, biochar addition under stressed conditions significantly improved the wheat growth and productivity. Briefly, it increased straw yield by 25%, 100-grain weight by 15% and grain yield by 10% compared to the control. Moreover, co-application of biochar with PGPRs B. thuringiensis, B. tropicus and B. paramycoides further enhanced straw yield by 37–41%, 100-grain weight by 30–36%, and grain yield by 22–22.57%, respectively. The co-application also enhanced soil quality by increasing plant-available phosphorus by 4–31%, microbial biomass by 33–45%, and soil K+/Na+ ratio by 41–44%. Conclusion Co-application of PGPRs and biochar alleviated plant drought stress by improving nutrient availability and absorption. Acting as a nutrient reservoir, biochar worked alongside PGPRs, who solubilized nutrients from the former and promoted wheat growth. We recommend that the co-application of suitable PGPRs and biochar is a better technology to produce wheat under drought conditions than using these enhancers separately.